Psychopathic Traits in a Swedish Court-Ordered Forensic Sample: Preferential Associations of Boldness, Meanness, and Disinhibition - Sörman, Karolina (International journal of offender therapy and comparative criminology, 2025)
The construct validity of the triarchic psychopathy model has yet to be evaluated in the Swedish forensic psychiatric context. We examined associations between the three phenotypic constructs of the triarchic model of psychopathy (i.e., boldness, meanness, disinhibition), self-assessed empathy and anxiety, and clinical variables in 91 individuals undergoing pretrial forensic psychiatric evaluation in Sweden. Participants completed the Triarchic Psychopathy Measure (TriPM) and self-report measures of empathy and anxiety. Clinical variables, including psychiatric diagnoses and criminal behavior, were collected from the forensic psychiatric evaluations (FPE). All three subscales of the TriPM displayed significant and predominantly anticipated correlations with empathy and trait anxiety measures. TriPM Disinhibition was the only subscale with significant associations with the clinical variables collected from the FPEs. The results provide evidence for the reliability and construct validity of the Swedish translation of the TriPM in a pretrial forensic setting.